Improving otoscopy education and diagnostic accuracy: A prospective interventional study. (November 2022) - Wauchope, J.; Garry, S.; Guinness, F.; Fitzsimons, J.; Heffernan, C.B.
Abstract: Objective: To assess and improve otoscopy examination skills across various medical specialities who perform otoscopy during their professional practice. Methods: A pre-intervention survey was created using www.surveymonkey.com, which included several preliminary questions to clarify the participant's speciality and training level, followed by 25 individual otoscopy images. The participants were given 12 possible diagnoses for each otoscopy image and asked to choose the single best answer. After completing the survey, participants were asked to watch an otoscopy teaching session. This teaching session was created with multidisciplinary feedback, and the content included a demonstration video and a didactic lecture. Finally, a post-intervention survey was circulated four weeks later to the same cohort of doctors to assess improvement. Results: A total of 79 pre-intervention surveys were collected with an average score of 53% (range 20–100%). The spectrum of medical specialities that completed the pre-intervention survey included paediatrics, ear, nose, and throat (ENT), emergency medicine, and general practice. The largest cohort of surveys came from senior house officers (SHO). In addition, 78.5% of responses were completed by doctors who had not worked in ENT before. After completing the otoscopy teaching session and at least four weeks after the initial survey, 23 post-intervention surveys were completed with an average score of 66% (range 32–100%), a 13% improvement. Conclusions: The results of the pre-intervention survey show that many doctors have difficulty diagnosing ear conditions. The implementation of a 25-min teaching session achieved a 13% improvement in the otoscopy knowledge of doctors across a variety of specialities.